Investigating the effect of age on platelet ultrastructure using transmission electron microscopy. Issue 6 (5th September 2019) - Tian, Ju; Cheng, Liu‐Hang‐Hang; Cui, Xiao; Lei, Xiao‐Xuan; Tang, Jian‐Bing; Cheng, Biao
Abstract: In the present study, the age‐ and sex‐related differences in platelet ultrastructure were investigated using transmission electron microscopy (TEM). A total of 15 healthy volunteers were grouped according to age, with 5 people in each of the following groups: young group (25‐45 years), middle‐aged group (46‐65 years), and old‐aged group (> 65 years). In the TEM micrographs, the internal components, specifically the α‐granules, dense granules, and lysosomal granules, of 20 platelets were counted for each group. Two‐way analysis of variance of age and sex variance was used to compare the results. The ultrastructure of the platelets in the old‐aged group was observed to be quite different from those of the young and middle‐aged groups. Specifically, with ageing, the platelet membrane becomes more irregular in shape and non‐smooth, and multiple platelet membrane ruptures are observed. Furthermore, the pseudopodia and protuberances become more numerous and slender, and the number of α‐granules is significantly reduced. These morphological changes indicate that ageing may affect the function of platelets, which in turn affects the efficacy of platelet concentrates. Thus, the effects of age should be considered when using platelet concentrates prepared from elderly autologous blood.